2017
DOI: 10.1016/j.ejps.2017.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Six month delivery of GDNF from PLGA/vitamin E biodegradable microspheres after intravitreal injection in rabbits

Abstract: Local long-term delivery of glial cell line derived neurotrophic factor (GDNF) from vitamin E/poly-lactic-co-glycolic acid microspheres (MSs) protects retinal ganglion cells in an animal model of glaucoma for up to 11weeks. However, the pharmacokinetics of GDNF after intravitreal injection of MSs is not known. We evaluated the GDNF levels after a single intravitreal injection of GDNF/VitE MSs. Biodegradable MSs were prepared by the solid-oil-in-water emulsion-solvent evaporation technique and characterized. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…The use of IVT injected nanoformulations has also been explored, such as the injection of basic fibroblast growth factor (FGF)-impregnated nanoparticles (NP) [ 4 ] or poly-lactic- co -glycolic acid (PLGA) microspheres containing NTs [ 18 ]. A single IVT injection of the glial cell-derived neurotrophic factor (GDNF) encapsulated in vitamin E/PLGA microspheres was found to protect RGCs in animal models of glaucoma for up to 11 weeks by providing the sustained controlled release of GDNF in a controlled fashion for up to 6 months [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of IVT injected nanoformulations has also been explored, such as the injection of basic fibroblast growth factor (FGF)-impregnated nanoparticles (NP) [ 4 ] or poly-lactic- co -glycolic acid (PLGA) microspheres containing NTs [ 18 ]. A single IVT injection of the glial cell-derived neurotrophic factor (GDNF) encapsulated in vitamin E/PLGA microspheres was found to protect RGCs in animal models of glaucoma for up to 11 weeks by providing the sustained controlled release of GDNF in a controlled fashion for up to 6 months [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies confirmed this system to be safe. These MS did not show abnormalities during a six-month follow up after intravitreal administration on adult female New Zealand albino rabbits [32].…”
Section: Neurotrophic Factorsmentioning
confidence: 69%
“…Nowadays, it is known that preservation of adequate protein folding, mitochondrial function, inflammation process and scavenging pathways directly avoids programmed cell death and irreversible damage of the neuronal cells [32]. Also, inhibition of retinal microglial and Müller glia activation via sigma-1 receptor agonism with neurosteroids (e.g., dehydroepiandrosterone, that has anti-inflammatory functions as well) has been described recently as an innovative and viable strategy [28].…”
Section: Introductionmentioning
confidence: 99%
“…10% GDNF-microsphere emulsion resulted in a significant reduction of optic nerve head excavation, and increased RGC survival, compared with 2% GDNF-microspheres, blank microspheres, and saline solution [205]. In order to evaluate the pharmacokinetics of GDNF, García-Caballero et al [206] analyzed its levels after a single intravitreal injection of GDNF/vitamin E microspheres in rabbits. This method allowed a sustained controlled release of GDNF for up to 6 months.…”
Section: Neuroprotection and Neuroregeneration And Neurotrophic Factorsmentioning
confidence: 99%